Cyclosporine A and steroid therapy in childhood steroid-resistant nephrotic syndrome - Tahar, Gargah (Dove Medical Press, 2010)
BACKGROUND: In children, idiopathic nephrotic syndrome (INS) is primarily treated using corticosteroids. When remission is not achieved, the coadministration of potent immunosuppressant therapy becomes imperative. Cyclosporine A (CsA) is reportedly associated with a higher incidence of remission in comparison with other immunosuppressive agents. METHODS: The present study investigated the response of combination therapy using CsA and prednisolone in 30 Tunisian children with idiopathic steroid-resistant nephrotic syndrome (ISRNS). Renal histopathology was compatible with focal segmental glomerular sclerosis (FSGS) in 15 children, minimal change disease (MCD) in nine children, and diffuses mesangiale proliferation (DMP) in six children. RESULTS: The therapy protocol produced a complete remission of proteinuria in 15 patients (50%) and a partial remission in nine patients (30%). Six patients (20%) showed no response to therapy. Progression to end stage renal disease occurred in five CsA-resistant children and in four CsA-responsive patients. CsA-related nephrotoxicity was detected by renal biopsy in one patient. CONCLUSIONS: CsA remains the primary cytotoxic treatment for childhood steroid-resistant nephrotic syndrome. Its use in combination with corticosteroids provides optimum efficiency without high risk of nephrotoxicity.